2023
DOI: 10.3389/fcimb.2023.1265011
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of three novel lytic phages against K54 serotype carbapenem-resistant hypervirulent Klebsiella pneumoniae

Chengju Fang,
Xiaoyi Dai,
Li Xiang
et al.

Abstract: The emergence of carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) has driven us to explore alternative treatments for the limitation of antimicrobial agents. Lytic phages are considered a promising alternative treatment for CR-hvKP infection. In this study, we reported three novel lytic phages, vB_KpnA_SCNJ1-Z, vB_KpnS_SCNJ1-C, and vB_KpnM_SCNJ1-Y, against a CR-hvKP strain SCNJ1, and they possess genomes of double-stranded DNA with a size of 43,428 bp, 46,039 bp, and 50,360 bp, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The one-step growth curves, optimal MOI, and stability results showed that the phages displayed relatively short latency periods (less than 10 minutes) and a lower MOI (0.1), with broad pH (4 to12) and thermal stabilities (-44 to 55°C) ( Figure 7 ). This implies that fewer CSP1 is required to rapidly absorb to the host surface and lyse more bacterial cells within a certain period, demonstrating the potential as a stable biological agent suitable for biocontrol applications ( Fang et al., 2023 ). Although phages with a broader host spectrum are generally more desirable, CSP1 did not affect more than half (33 out of 54) of the clinical MDR- C. striatum isolates tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-step growth curves, optimal MOI, and stability results showed that the phages displayed relatively short latency periods (less than 10 minutes) and a lower MOI (0.1), with broad pH (4 to12) and thermal stabilities (-44 to 55°C) ( Figure 7 ). This implies that fewer CSP1 is required to rapidly absorb to the host surface and lyse more bacterial cells within a certain period, demonstrating the potential as a stable biological agent suitable for biocontrol applications ( Fang et al., 2023 ). Although phages with a broader host spectrum are generally more desirable, CSP1 did not affect more than half (33 out of 54) of the clinical MDR- C. striatum isolates tested.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the culture was centrifuged (8000 rpm/min for 10 minutes) and the supernatant filtered through a 0.22 μm filter to remove bacteria, followed by determining the phage CSP1 titer (PFU/mL) (calculated as the number of CSP1 plaques on double-layer agar plates × dilution factor × 10). The highest phage release under different MOI ratios was recorded to determine the optimal MOI ( Fang et al., 2023 ). The assay was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%